Optimizing stunting prevention, disaster mitigation, and economic improvement in Tugubandung village - Maulana, Yusril Ihza; Aulia, Rima; Sonani, Nia; N, Muhammad Fathurrohman; Herdiantri, Nabila; Salamah, Naila Putri; Nurohmah, Vinda Amelia; Arjuna, M.; Alfarezi, Azril Ahmad; Bagas, Muhamad Fathir; Agusta, Muhammad Sinar; Ghibran, Muhamad; et al. (Jurnal Pengabdian West Science, 2025)
Tugubandung Village, located in Kabandungan District, Sukabumi Regency, holds great potential in agriculture and micro-enterprise sectors. However, the village also faces complex challenges, including child stunting, disaster risks such as landslides, limited economic capacity, and low digital literacy among MSMEs. Through the 2025 Community Service Program (KKN) of Nusa Putra University, students implemented participatory-based community empowerment with three main focuses: Two Actions Against Stunting, Disaster Mitigation “Planting Together, Saving Together”, and MSME Go Digital: Village Economic Transformation in the Technology Era. Supporting programs included child literacy development, anti-drug and HIV/AIDS education, clean and healthy living behavior, eco-print workshops, preservation of Sundanese culture through dongdang making, and the celebration of Indonesia’s 80th Independence Day. The results indicate significant improvements in nutritional awareness, disaster preparedness, and digital marketing skills among MSMEs. Additional programs also fostered greater awareness of environmental, health, and cultural values. With a collaborative approach among students, supervisors, local officials, and the community, the KKN program in Tugubandung Village has effectively enhanced human resource capacity and community resilience.